Experiments and Index Construction for Disaster Caused by Low Temperature Affecting Hetao Sunflower in Inner Mongolia - Duan Xiaofeng; Liu Wei; Bao Jiajing; Liu Yanli; Li Shuqi; Tang Hongyan (应用气象学报)
Sunflower is the fourth-largest oilseed crop. China ranks the sixth in the world of the planting area of sunflowers, and Hetao Irrigation Area in Inner Mongolia is one of the rare producing areas of high quality, developing into the largest planting base and specially distributed center of sunflowers. However, the damage caused by freezing significantly hinders the industry's development. How to prevent or mitigate freezing damage has become a significant challenge for the sustainable development of the industry. Therefore, the main varieties of Hetao sunflower with developmental potential are investigated. In August and September of 2023, artificial simulation tests are conducted as the primary focus. Field tests for freezing damage and investigations into natural freezing damage are conducted as secondary assessments. Supercooling abilities of sunflower leaves, stalks, and seeds at various sowing periods are compared and analyzed through artificial simulations and field supplementary experiments. The freezing rate of sunflowers under various low-temperature conditions is analyzed, and the quantitative relationship between adverse conditions and freezing rates is examined. The regression analysis method is employed to develop and validate disaster grade indices based on harmful accumulated temperature and ordinal numbers. Results indicate that sunflower seeds exhibit the highest supercooling ability and cold resistance, followed by stems and leaves. The older the seedling and leaf age, the greater the frost resistance is; conversely, younger seedlings and leaves exhibit weaker frost resistance. The variation in cold resistance among different parts is greater than the variation caused by different sowing methods. The critical freezing temperature of sunflower plants is -1 ℃. The lower the temperature and the longer the duration, the greater the degree of freezing is. Harmful accumulated temperature values for sunflower plants exhibiting light, medium, and severe freezing damage demonstrate an increasing trend across three sowing periods. When the same freezing damage grade is reached, a delay in the sowing date results in a decrease in seedling age, as well as a reduction in the required cumulative harmful temperature. On the contrary, as the age of the seedling and leaves increase, the amount of harmful accumulated temperature required also increases. Under the same freezing damage grade, seeds require the highest accumulated temperature during the sowing period, followed by stems and leaves. It is proved that the harmful accumulated temperature indices can reasonably and objectively reflect the freezing condition of sunflower, which can provide a scientific basis for meteorological services such as early warning and evaluation of freezing damage in autumn for Hetao sunflower.